Development of a System to Assist Automatic Translation of Hand-Drawn Maps into Tactile Graphics and Its Usability Evaluation - Jianjun Chen; Noboru Takagi (Advances in Fuzzy Systems)
Tactile graphics are images that use raised surfaces so that a visually impaired person can feel them. Tactile maps are used by blind and partially sighted people when navigating around an environment, and they are also used prior to a visit for orientation purposes. Since the ability to read tactile graphics deeply depends on individuals, providing tactile graphics individually is needed. This implies that producing tactile graphics should be as simple as possible. Based on this background, we are developing a system for automating production of tactile maps from hand-drawn figures. In this paper, we first present a pattern recognition method for hand-drawn maps. The usability of our system is then evaluated by comparing it with the two different methods to produce tactile graphics.